Blood Glutamate Levels Are Closely Related to Acute Lung Injury and Prognosis after Stroke - Bai, Wei; Li, Wei; Ning, Ya-Lei; Li, Ping; Zhao, Yan; Yang, Nan; Jiang, Yu-Lin; Liang, Ze-Ping; Jiang, Dong-Po; Wang, Ying; Zhang, Meng; Zhou, Yuan-Guo (Frontiers in Neurology, 2018)
Background: Acute lung injury (ALI) is a serious complication of stroke that occurs with a high incidence. Our preclinical results indicated that ALI might be related to blood glutamate levels after brain injury. The purpose of the present study was to assess dynamic changes in blood glutamate levels in patients with stroke and to determine the correlation between blood glutamate levels, ALI and long-term prognosis after stroke. Methods: Venous blood samples were collected from controls and patients with stroke at admission and on the 3rd and 7th day after the onset of stroke. Patients were followed for three months. The correlations among blood glutamate levels, severities of stroke and ALI, and long-term outcomes were analysed, and the predictive values of blood glutamate levels and severity scores for ALI were assessed. Results: In this study, a total of 384 patients with stroke were enrolled, with a median age of 59 years. Patients showed significantly increased blood glutamate levels within 7 days of stroke onset (p<0.05), and patients with more severe injuries showed higher blood glutamate levels. Moreover, blood glutamate levels were closely related to the occurrence (adjusted odds ratio [OR], 3.022, p=0.003) and severity (p<0.001) of ALI and the long-term prognosis after stroke (p<0.05), and they were a more accurate predictor of ALI than the more commonly used severity scores (p<0.01). Conclusions: These results indicated that an increased blood glutamate level was closely related to the development of ALI and a poor prognosis after stroke. Trial registration: ChiCTR-RPC-15006770 (http://www.chictr.org.cn)